Transformative Educational Actions for Children in Poverty: Sen’s Capability Approach into Practice in the Korean Context - Kim, Kyung Hi (Education as Change, 2017)
By adopting Senâ€™s capability approach, this study explores transformative educational actions for children in poverty to develop their capabilities for learning for life. Senâ€™s capability approach provides a framework for why it is important to foster the capabilities of children in poverty and what is required to help these children to improve their capabilities for life. With the use of critical communicative methodology, transformative educational actions were positioned to foster expansive capabilities for life. This study suggests that the issue of poverty and its impact on children and education equality can be better tackled from the perspective of capability enhancement.Â